Fuse electrode and high safety lithium ion battery
Patent Information
- Application Number
- CN202611092806.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-22
- Publication Date
- 2026-10-23
AI Technical Summary
这种结构的电池,当其极组内部某位置因某种原因发生内部短路时,会形成较大的内部短路电流,造成电池内部剧烈升温,将引起电池热失控,因此如何提升锂离子电池的本质安全是一项重要课题
1、本发明所述保险丝电极,具备特殊设计的集流体活性材料未涂覆区域,并且在所述区域设置了特殊设计的孔隙,具备这种结构的电极能够在电池内部或外部发生短路异常时,通过所述电极分区之间的电极连接限制电池内部其他区域流向电池内部短路位置的电流,并在内部短路电流达到一定程度时发生熔断,从而减缓或阻断内部短路的继续发生,避免电池热失控,有效提升电池的本质安全性。
Smart Images

Figure CN122968619A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of lithium-ion battery manufacturing technology, and specifically relates to a fuse electrode and a high-safety lithium-ion battery. Background Technology
[0002] Lithium-ion batteries are widely used in automobiles, energy storage, smart terminals, and portable electrical appliances due to their advantages such as high energy density, high power density, long cycle life, no memory effect, and environmental friendliness. However, in recent years, the large-scale application of lithium-ion batteries has brought about many serious safety problems. When lithium-ion batteries malfunction, they are highly susceptible to thermal runaway, leading to serious fires and explosions, causing product damage and even personal injury.
[0003] Typically, external protection designs for lithium-ion batteries, including protection circuits and casing protection, can protect them from external factors. These designs are effective against mechanical damage caused by external impacts, compression, and deformation, as well as electrical / thermal damage caused by abuse such as overcharging, over-discharging, external short circuits, overloads, and overheating. However, these methods are often ineffective against thermal runaway caused by short circuits inside the battery.
[0004] Currently, the lithium-ion battery industry typically uses positive and negative electrodes, along with a separator placed between them, to assemble the battery electrode assembly using stacking or winding methods. This assembly is then housed in a casing to manufacture a lithium-ion battery. With this structure, if an internal short circuit occurs at some point within the electrode assembly for any reason, a large internal short-circuit current will be generated, causing a rapid increase in internal temperature and potentially leading to thermal runaway. Therefore, improving the intrinsic safety of lithium-ion batteries is a crucial issue. Summary of the Invention
[0005] This invention proposes a fuse electrode and a high-safety lithium-ion battery, as well as a lithium-ion battery manufactured using this electrode. This design significantly increases the intrinsic safety of the battery without compromising its electrochemical performance. When an unexpected internal / external factor induces an internal short circuit, the connection points of each section of the fuse electrode will significantly limit the current flowing from other sections of the battery to the short-circuited section, and will melt when the internal short-circuit current reaches a certain level, thereby slowing down or preventing the continued occurrence of the internal short circuit and avoiding battery thermal runaway.
[0006] This invention is achieved using the following technical solution: A fuse electrode and a high-safety lithium-ion battery include a current collector and an active material coated on the current collector. The active material is coated on the surface of the current collector and has a current collector blank area. The current collector blank area has pores, and an insulating coating is disposed on the surface of the current collector blank area where the pores are located.
[0007] The current collector blank area is a strip-shaped area with a width of 0.2~20mm. The strip-shaped area divides the active material coating area into several coating zones according to the rule of equal division.
[0008] The pores in the blank area of the current collector can be circular, strip-shaped, triangular, square, polygonal, or other shapes.
[0009] The diameter of the circular pores is between 0.1 and 20 mm.
[0010] The width of the strip pores is between 0.1 and 20 mm, and the length of the strip pores does not exceed the dimensions of any planar dimension of the positive electrode sheet.
[0011] The area of triangular and square pores ranges from 0.01 to 100 mm².
[0012] The insulating coating is composed of one or more of alumina, burlite, zirconium dioxide, silica, polyethylene, polypropylene, polyurethane, and polyvinylidene fluoride, mixed with one or more of polyvinylidene fluoride, polytetrafluoroethylene, and polyacrylate. The thickness of the insulating coating is 0.1~10μm, and the area of the insulating coating needs to completely cover the current collector blank area of the electrode sheet and extend beyond the electrode active material coating area by 0.1~2.0mm.
[0013] According to the morphological characteristics of the electrode sheet, the current collector blank area is evenly divided into 2 to 20 active material coating areas, and the area and shape of the separated active material coating areas are similar or equal.
[0014] The distance between the pores is between 0.2 and 100 mm.
[0015] The insulating coating is achieved through conventional coating processes such as gravure printing, slot coating, and transfer coating.
[0016] The lithium-ion battery manufactured using the above-described technical solution of the present invention has the following beneficial effects: 1. The fuse electrode of the present invention has a specially designed uncoated area of the current collector active material, and specially designed pores are provided in the area. When a short circuit occurs inside or outside the battery, the electrode can limit the current flowing from other areas inside the battery to the short circuit location inside the battery through the electrode connection between the electrode partitions, and melt when the internal short circuit current reaches a certain level, thereby slowing down or blocking the continued occurrence of the internal short circuit, avoiding battery thermal runaway, and effectively improving the intrinsic safety of the battery.
[0017] 2. The high-safety lithium-ion battery described in this invention uses a fuse electrode that is applicable to various types of batteries with different structures, sizes, and capacities. Through flexible design of electrode manufacturing and pore forming processes, it can be widely used in various lithium-ion batteries. Furthermore, since it does not significantly affect the current collector effect or change the battery's electrochemical system, it has almost no impact on the battery's electrochemical performance. Compared to other current technologies that reduce battery performance, it has a significant performance advantage. Attached Figure Description
[0018] Figure 1 This is a schematic diagram of the manufacturing process of the positive electrode of the fuse described in this invention; Figure 2 This is a schematic diagram of the battery structure using fuse electrodes according to the present invention; Figure 3 This is a schematic diagram of the positive electrode sheet in Embodiment 1 of the present invention; Figure 4 This is a schematic diagram of the positive electrode sheet in Embodiment 2 of the present invention; Figure 5 This is a schematic diagram of the positive electrode sheet in Embodiment 3 of the present invention; Figure 6 This is a schematic diagram of the positive electrode sheet in Embodiment 4 of the present invention; Explanation of reference numerals in the attached figures: 1—Electrode slurry coating process; 2—Electrode drying process; 3—Electrode rolling process; 4—Electrode laser engraving process; 5 – Electrode die-cutting process; 6 – Electrode sheet receiving process; 7 – Battery casing; 8 – Battery fuse positive terminal; 9 – Battery separator; 10 – Battery fuse negative terminal; 11 - Battery lower casing. Detailed Implementation
[0019] The present invention will now be described in further detail with reference to the accompanying drawings and embodiments.
[0020] The accompanying drawings are provided to further illustrate the invention and form part of the specification. They are used together with the following detailed description to explain the invention, but do not constitute a limitation thereof.
[0021] To provide a clearer understanding of the technical features, objectives, and beneficial effects of the present invention, the technical solution of the present invention will now be described in detail with reference to the accompanying drawings, but this should not be construed as limiting the scope of implementation of the present invention.
[0022] For experiments not specifically described in the examples, the procedures or conditions should be followed according to the conventional experimental procedures described in the literature in this field. Reagents or instruments whose manufacturers are not specified are all commercially available conventional reagent products.
[0023] Reference Figure 1 The diagram shows a schematic of the manufacturing process of the positive electrode of the fuse according to Embodiment 1 of the present invention. The positive electrode slurry, designed and mixed according to industry-standard processes, is first coated onto the current collector, then thoroughly dried in a heated oven, followed by a rolling process to compact the electrode. A laser is then used to engrave holes in the coated blank current collector area. Finally, the electrode is die-cut to obtain the positive electrode of the fuse before assembly. Figure 3 ).
[0024] refer to Figure 2 The diagram shown is a schematic representation of the battery structure using a fuse electrode according to the present invention. The battery internally consists of a fuse positive electrode, a fuse negative electrode, and a separator disposed therebetween, and is then encapsulated by an upper battery casing and a lower battery casing to form the battery.
[0025] refer to Figure 3 The diagram shown is a schematic of the positive electrode in Embodiment 1 of the present invention. The electrode uses a 15μm thick aluminum foil as the current collector. Uncoated areas of the current collector active material, each 5mm wide, are provided at 1 / 3 and 2 / 3 of the electrode length direction. An alumina coating of 5-20μm thickness is deposited on the surface of these areas. Circular pores with a diameter of 2mm are manufactured using laser engraving. These pores are distributed in a straight line within the 5mm wide uncoated current collector area, with a spacing of 1mm between adjacent pores.
[0026] refer to Figure 4 The diagram shown is a schematic of the positive electrode sheet in Embodiment 2 of the present invention. A 12μm thick aluminum foil is used as the current collector. A grid-shaped pattern consisting of 1mm diameter pores is formed on the positive electrode sheet, dividing it into nine equal parts with a pore spacing of 0.5mm. A polyvinylidene fluoride layer with a width of 2mm and a thickness of 1-5μm is placed in each of the two transverse and two longitudinal pore areas.
[0027] refer to Figure 5 The diagram shown is a schematic of the positive electrode sheet in Embodiment 3 of the present invention. A series of intersecting strip-shaped perforations are formed on the positive electrode sheet. The width of each strip-shaped perforation is 1 mm, and the intersecting strip-shaped perforations divide the positive electrode sheet into several small regions. The length of the strip-shaped perforations is set such that the maximum width of the aluminum foil current collector between each small region is 3 mm.
[0028] refer to Figure 6The diagram shown is a schematic of the positive electrode sheet in Embodiment 4 of the present invention. The positive electrode sheet is a strip-shaped electrode sheet with a width of 50 mm and a length of 420 mm. It is divided into 10 parts by 9 polyethylene coating areas. The diameter of the pores on the polyethylene coating is 1 mm, the spacing is 0.5 mm, and the distance between the pores and the edge of the electrode sheet is 2-5 mm.
[0029] This invention proposes a high-safety lithium-ion battery, comprising a positive electrode, a negative electrode, a separator disposed between the positive and negative electrodes, an electrolyte, and a casing. The positive electrode, negative electrode, and separator are assembled into a cylindrical or square lithium-ion battery structure using industry-standard stacking or winding processes. The materials used in the high-safety lithium-ion battery, including electrode active materials, current collector materials, electrolyte materials, and battery casing materials, are all industry-standard materials. The positive and negative electrodes of the high-safety lithium-ion battery are designed as fuse electrodes. The fuse electrode includes a current collector and an active material coated on the current collector, as well as a certain number and shape of pores disposed on the electrode. The fuse electrode is divided into a certain number of electrode partitions by the pores, and the electrode partitions are connected by electrode regions between the pores. The number of electrode partitions is 2 to 20, with similar or equal areas and shapes. The pores are positioned within the uncoated area of the active material in the electrode current collector, and the width of the uncoated area is 1 to 20 mm, extending to the edge of the electrode. The number of pores can be designed based on the shape of the fuse electrodes and the arrangement of the pores separating the fuse electrodes, ranging from 1 to 100. The pore shapes can be circular, strip-shaped, triangular, square, or other polygonal shapes. The diameter of the circular pores is between 0.1 and 20 mm; the width of the strip-shaped pores is between 0.1 and 20 mm; and the area of the triangular and square pores is between 0.01 and 100 mm². 2 The distance between adjacent pores is 0.5~100mm. An insulating coating is provided on the surface of the uncoated area of the current collector active material. The thickness of the insulating coating is 0.1~100μm, and it completely covers the uncoated area of the current collector active material. The insulating coating is composed of one or more of alumina, boehmite, zirconium dioxide, silica, polyethylene, polypropylene, polyurethane, and polyvinylidene fluoride, and a mixture of one or more of polyvinylidene fluoride, polytetrafluoroethylene, and polyacrylate.
[0030] Example 1: This embodiment provides a high-power, high-safety polymer lithium-ion battery. Lithium cobalt oxide, conductive carbon black, and polyvinylidene fluoride are uniformly mixed in a ratio of 95:2:3, and then a certain amount of polymethylpyrrolidone is added and stirred uniformly to form a positive electrode slurry. This slurry is then coated onto a 15μm thick aluminum foil current collector using a coating machine, with the coating surface density set to 100g / m².2 Simultaneously, uncoated areas of 5mm width for the current collector active material are set at 1 / 3 and 2 / 3 of the electrode length, and an alumina coating with a thickness of 5-20μm is applied to the surface of these areas. The negative electrode uses a commercially available artificial graphite formulation to prepare the electrode paste, which is coated onto an 8μm thick copper foil current collector, with a coating areal density set to 52g / m². 2 Simultaneously, uncoated areas of 8 mm width for the current collector active material are set at 1 / 3 and 2 / 3 of the electrode length, and an alumina coating with a thickness of 5-20 μm is applied to the surface of these areas. After normal rolling of the coated positive and negative electrodes, circular pores with a diameter of 2 mm are created in the current collector area coated with alumina using laser engraving. These pores are distributed in a straight line in a 5 mm wide blank area for the current collector, with a spacing of 1 mm between adjacent pores. Then, the electrodes are cut into electrode sheets using an electrode shearing die. The fabrication process flow diagram is shown below. Figure 1 As shown, the prepared electrode sheet is as follows Figure 3 As shown.
[0031] Using the aforementioned positive and negative electrode sheets and a 16μm thick separator, the electrodes are assembled into an electrode group with opposite tabs using a common stacking method. Then, the positive and negative electrode tabs are welded together, and the battery is encapsulated using an industry-standard aluminum-plastic composite film. After conventional processes such as electrolyte injection and formation, an 8000mAh power-type soft-pack lithium-ion battery is produced. Its structural schematic diagram is shown below. Figure 2 As shown.
[0032] In this embodiment, the power-type soft-pack lithium-ion battery, during a nail penetration test, will create an internal short circuit at the point of penetration when the steel nail penetrates the center of the battery, generating a large internal short-circuit current. However, the presence of pores on both sides of the penetration point on the positive and negative electrodes limits the current of the internal short circuit, effectively reducing heat generation at the short-circuit location, preventing a rapid rise in battery temperature, blocking thermal runaway, and greatly improving battery safety.
[0033] Example 2: This embodiment provides an ultra-high rate, high-safety polymer lithium-ion battery. Commercially available nickel-cobalt-manganese lithium oxide is uniformly mixed into a positive electrode slurry according to a commonly used formulation ratio, and then coated onto a 12μm thick aluminum foil current collector. The coating surface density is set to 70 g / m². 2 A grid-shaped dotted pattern consisting of 1mm diameter holes is created on the positive electrode plate, dividing it into nine equal parts, with a hole spacing of 0.5mm. Figure 4 As shown, a polyvinylidene fluoride layer with a width of 2 mm and a thickness of 1~5 μm is set in each of the two horizontal pore dashed lines and the two vertical pore dashed lines.
[0034] Using the aforementioned positive electrode and lithium-ion battery negative electrode, and a 12μm thick polyethylene separator (with a 2μm layer of aluminum oxide nano-ceramic on its surface), the electrodes are assembled into an electrode group with tabs on the same side using a common stacking method. Then, the positive and negative electrode tabs are welded separately, and the battery is encapsulated using an industry-standard aluminum-plastic composite film. After conventional processes such as liquid injection and formation, an ultra-high rate soft-pack lithium-ion battery with a capacity of 2500mAh is produced.
[0035] In this embodiment, when the ultra-high rate soft-pack lithium-ion battery is subjected to a nail-puncture test in any area enclosed by the corresponding positive electrode plate pores on the battery surface, the ultra-high rate characteristic of this battery causes a large short-circuit current to instantly melt the current collector gap between the pores around the nail-puncture position of the positive electrode plate, thereby directly interrupting the continued occurrence of the internal short circuit, blocking the occurrence of battery thermal runaway, and greatly improving the safety of the battery.
[0036] Example 3: This embodiment provides a high-safety, square-shell aluminum-cased lithium-ion battery for power applications. Commercially available lithium iron phosphate material is uniformly stirred into a slurry using a commercial formulation, and then coated onto a 12μm thick aluminum foil current collector. The coating surface density is set to 170 g / m². 2 After the positive electrode sheet roll undergoes the normal rolling process, it is knurled using a knurling machine with cross-shaped grooves, and then the sheet is produced by positioning and shearing. Figure 5 The positive electrode shown has a cross-shaped pore width of 1 mm, and the cross-shaped pores divide the positive electrode into several small regions. The length of the pores is set so that the maximum width of the aluminum foil current collector between each small region is 3 mm.
[0037] Using the aforementioned positive electrode and lithium-ion battery negative electrode, a 9μm thick polyethylene separator is used, with a 2μm layer of aluminum oxide nano-ceramic on its surface and a 1~5μm thick polyvinylidene fluoride coating on both sides. The electrodes are assembled into an electrode group with tabs on the same side by stacking, and then a 120Ah high-safety square aluminum-cased lithium-ion battery is produced using the commonly used square aluminum shell manufacturing process.
[0038] The high-safety square aluminum-cased lithium-ion battery in this embodiment can be subjected to nail penetration tests at any location. Since the positive electrode areas are connected only by a small area of aluminum foil current collector, the internal short circuit caused by the nail penetration will quickly melt and sever the connection points between the affected area and the surrounding areas, preventing further internal short circuits. Simultaneously, other areas of the battery can continue to operate, performing effective charging and discharging. This not only greatly improves battery safety but also avoids power outages caused by sudden malfunctions.
[0039] Example 4: This embodiment provides a wound, high-safety, square, pouch-type lithium-ion battery. Commercially available lithium nickel cobalt manganese oxide material is formulated into a slurry using a commercial formulation, and then coated onto a 10μm thick aluminum foil current collector. The coating areal density is set to 230 g / m². 2 During coating, a 2mm wide polyethylene coating with 40mm intervals is applied to the electrode surface. After normal drying, the positive electrode roll undergoes a normal rolling process. Then, the polyethylene coating area of the positive electrode is stamped using a die with longitudinal perforations. It is then cut into strips 50mm wide and 420mm long. The electrode is divided into 10 sections by 9 polyethylene coating sections. A 1mm diameter perforation is created on the polyethylene coating of the positive electrode, spaced 0.5mm apart, with the perforation 2-5mm from the edge of the electrode. A schematic diagram of the electrode is shown below. Figure 6 As shown.
[0040] Using the aforementioned positive electrode and a conventional wound lithium-ion battery negative electrode, a 7μm thick separator with a 2μm layer of boehmite on its surface is assembled into an electrode group with tabs on the same side by winding. Then, a square soft-pack lithium-ion battery with a capacity of 7Ah is produced using a commonly used square winding manufacturing process.
[0041] In this embodiment, the external resistance of the square soft-pack lithium-ion battery can be adjusted to below 5mΩ during high-temperature short-circuit testing. Since the strip-shaped positive electrode sheet in this embodiment is divided into several regions by holes arranged in a straight line, when an external short circuit occurs, the regions of the positive electrode sheet are only connected through a small area of aluminum foil current collector. Therefore, the short-circuit current will be limited, which restricts the temperature rise caused by internal overcurrent and avoids thermal runaway of the battery.
[0042] The above specific implementation examples further illustrate the invention in detail. The pores on the positive and negative electrode plates can be flexibly designed according to the battery size, capacity, material system, and application scenario. Applying the lithium-ion battery fuse electrode described in this invention can effectively mitigate or block the rapid temperature rise caused by internal short circuits, thereby avoiding thermal runaway and effectively improving the intrinsic safety of lithium-ion batteries.
[0043] The embodiments described above do not constitute a limitation on the protection of this technical solution. For those skilled in the art, several simple deductions or substitutions can be made without departing from the concept of this invention, and all such deductions or substitutions should be considered to fall within the protection scope of this invention.
Claims
1. A fuse electrode and a high-safety lithium-ion battery, comprising a current collector and an active material coated on the current collector, characterized in that, An active material is applied to the surface of the current collector, which has a blank area. The blank area has pores, and an insulating coating is applied to the surface of the blank area where the pores are located.
2. The fuse electrode and high-safety lithium-ion battery according to claim 1, characterized in that, The current collector blank area is a strip-shaped area with a width of 0.2~20mm. The strip-shaped area divides the active material coating area into several coating zones according to the rule of equal division.
3. The fuse electrode and high-safety lithium-ion battery according to claim 1, characterized in that, The pores in the blank area of the current collector are circular, strip-shaped, triangular, or square polygonal.
4. The fuse electrode and high-safety lithium-ion battery according to claim 3, characterized in that, The diameter of the circular pores is between 0.1 and 20 mm.
5. The fuse electrode and high-safety lithium-ion battery according to claim 3, characterized in that, The width of the strip pores is between 0.1 and 20 mm, and the length of the strip pores does not exceed the dimensions of any planar dimension of the positive electrode sheet.
6. The fuse electrode and high-safety lithium-ion battery according to claim 3, characterized in that, The area of triangular and square pores ranges from 0.01 to 100 mm².
7. The fuse electrode and high-safety lithium-ion battery according to claim 1, characterized in that, The insulating coating is composed of one or more of alumina, burlite, zirconium dioxide, silicon dioxide, polyethylene, polypropylene, polyurethane, and polyvinylidene fluoride, mixed with one or more of polyvinylidene fluoride, polytetrafluoroethylene, and polyacrylate. The thickness of the insulating coating is 0.1~10μm, and the area of the insulating coating needs to completely cover the current collector blank area of the electrode sheet and extend beyond the electrode active material coating area by 0.1~2.0mm.
8. The fuse electrode and high-safety lithium-ion battery according to claim 2, characterized in that, According to the morphological characteristics of the electrode sheet, the current collector blank area is evenly divided into 2 to 20 active material coating areas, and the area and shape of the separated active material coating areas are similar or equal.
9. The fuse electrode and high-safety lithium-ion battery according to claim 3, characterized in that, The distance between the pores is between 0.2 and 100 mm.
10. The fuse electrode and high-safety lithium-ion battery according to claim 1, characterized in that, The insulating coating is achieved through conventional coating processes such as gravure printing, slot coating, and transfer coating.